Perancangan dan Evaluasi Sistem Informasi Pengendalian Rekam Medis Berbasis Website menggunakan User Experience Questionnaire (UEQ) - Mochammad Arief Darmawan (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2022)
Borrowing and returning medical records is part of the medical record system in health facilities. One of them is that some puskesmas are less than optimal in borrowing and returning medical records because the recording process is still manual. This causes several problems, one of which is that the filling officer has difficulty in monitoring the presence of medical records entering and leaving the filling room. The medical record control information system is an information system that has a positive impact on the process of borrowing and returning medical records. Medical records that come out of the filling room must be recorded properly as well as the return of medical records because medical records are confidential documents. So that the control of medical records is important in the implementation of health services, especially in the field of medical records. This research is a qualitative research with action research research methods. The design of the medical record control information system uses flowchart diagrams, context diagrams, data flow diagrams, entity relationship diagrams, wireframes and user interfaces. Meanwhile, to evaluate the medical record control information system using the User Experience Questionnaire (UEQ).